Saving capitalism for the many, not the few - Reich, Robert B. (New York Penguin, 2016)
America was once celebrated for and defined by its large and prosperous middle class. Now, this middle class is shrinking, a new oligarchy is rising, and the country faces its greatest wealth disparity in eighty years. Why is the economic system that made America strong suddenly failing us, and how can it be fixed?
Includes bibliographical references (pages 222-263) and index.
Keywords: Capitalism--United States